Evidence of physiotherapeutic interventions for acute LBP patients - Q. Louw; L. Morris; J. Sklaar (AOSIS, 2007)
Objective: To identify the current evidence for acute low back pain (LBP) treatment techniques and to amalgamate this information into a clinically applicable algorithm for South African physiotherapists.Study design: Systematic review.Methods: Computerized bibliographical databases were systematically searched during September 2006 and October 2006 for primary and secondary research reporting on the efficacy of various physiotherapeutic treatment techniques for acute LBP. A search for clinical guidelines regarding acute LBP was also undertaken. Evidence levels were allocated to the primary and secondary research retrieved. Results: Twenty-one systematic reviews, four randomized controlled trials and eleven clinical guidelines were included in this review. There is Level 1 evidence that advice to stay active, McKenzie preferential exercises and spinal manipulative therapy (up to six weeks) is beneficial in the initial treatment of acute LBP. There is level 2 evidence that stability exercises, dry needling, heat wrap with exercises, cognitive behavioural therapy, printed patient education, massage (with education and exercises), and lifestyle modification might be potentially beneficial in the treatment of acute LBP. There is level 1 evidence that bed rest should not be recommended for simple acute LBP.  Should a patient not resolve in six weeks, red and yellow flags should be re-assessed, or patient should be referred to a specialist. Outcome: Based on the current evidence, a composite algorithm was developed to assist South African physiotherapists when making treatment decisions for acute LBP. Conclusion: There seems to be a lack of evidence for the efficacy of common treatment techniques used by physiotherapists in the management of acute LBP, indicating an urgent need for physiotherapy-specific, high-quality clinical trials. It is suggested that the evidence-based algorithm that has been developed, be used in the management of acute LBP to standardize physiotherapy intervention in South Africa.